Analiza prawnoporównawcza przepisów dotyczących zjawiska fałszerstwa dzieł sztuki w prawie polskim i włoskim = Comparison of polish and italian regulations related to forgery of the pieces of art - Klimczyk, Agata (Journal of Education, Health and Sport, 2016)
Klimczyk Agata. Analiza prawnoporównawcza przepisów dotyczących zjawiska fałszerstwa dzieł sztuki w prawie polskim i włoskim = Comparison of polish and italian regulations related to forgery of the pieces of art. Journal of Education, Health and Sport. 2016;6(10):236-252. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.161054 http://ojs.ukw.edu.pl/index.php/johs/article/view/3937 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 15.10.2016. Analiza prawnoporównawcza przepisów dotyczących zjawiska fałszerstwa dzieł sztuki w prawie polskim i włoskim Comparison of polish and italian regulations related to forgery of the pieces of art Agata Klimczyk Uniwersytet Mikołaja Kopernika w Toruniu Nicolaus Copernicus University in Torun Streszczenie Celem pracy było porównanie polskiego i włoskiego systemu prawnego i wskazanie możliwych rozwiązań. Proceder fałszerstw dzieł sztuki będzie pojawiał się coraz częściej. Związane jest to przede wszystkim ze wzrostem cen obiektów oraz z otwartością rynku antykwarycznego, także z lukami w prawie, pozwalającymi na manipulację. W przypadku zakupów przedmiotów o niebagatelnej kwocie, konieczne jest przeprowadzenie fachowej ekspertyzy. Należy zwrócić uwagę, że w polskim systemie prawnym brakuje regulacji o charakterze szczegółowym, a w wielu przypadkach stosowane są ogólne przepisy dotyczące oszustw, fałszerstw etc. Porównując regulacje obowiązujące w obu systemach prawnych należy stwierdzić, że w RP brakuje, np., przepisu dotyczącego publikacji danych osobowych sprawców, co jest bardzo istotne ze względu na konieczność zaufania do sprzedawców dzieł sztuki ze strony nabywców. Abstract The aim of the work was to compare the Polish and Italian legal system and an indication of the possible solutions. Practice counterfeit works of art will appear more often. This is mainly due to increase in prices of properties and antique market openness, also with gaps in the law, allowing for manipulation. In the case of purchases of items with a considerable amount, it is necessary to carry out professional expertise. It should be noted that in the Polish legal system lacks a regulation of a specific, and in many cases used are general provisions on fraud, counterfeiting, etc. Comparing regulations in both legal systems, it should be noted that in Poland are missing, for example, the provision on the publication of personal data of the perpetrators, which is very important because of the need to trust the sellers of works of art on the part of the buyers. Słowa kluczowe: fałszerstwo, prawo, dzieła sztuki Key words: forgery, law, pieces of art